2019
DOI: 10.1016/j.joca.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy computed tomography in calcium pyrophosphate deposition: initial clinical experience

Abstract: Objective: To determine the dual-energy computed tomography (DECT) attenuation properties of meniscal calcifications in calcium pyrophosphate deposition (CPPD) in vivo, and assess whether DECT was able to discriminate meniscal CPP deposits from calcium hydroxyapatite (HA) in subchondral and trabecular bone. Method: Patients with clinical suspicion of crystal-related arthropathy (gout and/or CPPD) and knee DECT scans were retrospectively assigned to CPPD (n ¼ 19) or control (n ¼ 21) groups depending on the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 21 publications
0
54
1
Order By: Relevance
“…The present study addressed one of the issues recently raised by the first clinical use of DECT in CPPD (7,(9)(10)(11): does early calcium crystal deposition alter DECT attenuation characteristics in menisci and articular cartilage prior to the appearance of detectable chondrocalcinosis by conventional CT? In this study, with a large enough sample size to detect clinically relevant changes in DECT attenuation characteristics, we found that with currently available DECT technology (7), the answer was no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study addressed one of the issues recently raised by the first clinical use of DECT in CPPD (7,(9)(10)(11): does early calcium crystal deposition alter DECT attenuation characteristics in menisci and articular cartilage prior to the appearance of detectable chondrocalcinosis by conventional CT? In this study, with a large enough sample size to detect clinically relevant changes in DECT attenuation characteristics, we found that with currently available DECT technology (7), the answer was no.…”
Section: Discussionmentioning
confidence: 99%
“…P values were adjusted for each parameter within zone categories/knee structures (menisci, articular cartilage) using Holm's technique to avoid α risk inflation due to repeated comparisons of the same parameters and groups within zones. Additional details on the statistical methods have been published previously (7). The correlation between the calcification area within ROIs and DEI, rho, and Z eff was evaluated using Spearman's correlation coefficient including 95% confidence intervals (95% CIs).…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the slight inferior implant survival rate in patients with histologically proven CC compared to radiologically diagnosed CC found by Kumar et al [22], one could argue that the preoperative diagnosis of CC, except for patients with clinical manifestation of inflammation, is usually established based on radiographic findings and not on histology, which questions the clinical relevance of this finding. On the other hand, the presence of CPP crystals either in the synovial fluid or in the cartilage, not yet visible on plane radiographs could be diagnosed non-invasively especially with ultrasound, which has a better sensitivity compared to plain radiographs, or with MRI or with dualenergy CT [30][31][32][33][34].…”
Section: Ukamentioning
confidence: 99%
“…Dual-energy CT or multi-energy spectral photon-counting CT could have been key factors to analyze the causing crystals, show multi-crystal involvement, and show differential diagnoses, e.g. hydroxyapatite crystal deposits [40][41][42]. One final limitation is that we did not include a control group of aspiration negative diagnosis, because a high false negative rate for CPPD crystal analysis is known in the literature.…”
Section: Limitationsmentioning
confidence: 99%